Phytochemical Screening and Quality of Crescentia cujete L. Leaf Extract - Julia Putri Ayunda; Makhabbah Jamilatun; Pradea Indah Lukito (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Crescentia cujete L., known as maja, has traditionally been used as a medicinal plant in several countries. The fruit and other parts of this plant contain bioactive compounds with antioxidant, antibacterial, antidiabetic, anti-inflammatory, and cytotoxic activities related to their secondary metabolites. The purpose of this study was to determine the quality of Crescentia cujete L. leaf extract obtained from Gajahan Hamlet, Pasuruan. This study used an experimental method, which included organoleptic tests, water- and ethanol-soluble extract levels, water content, ash content, and phytochemical screening. The results showed that the yield of Crescentia cujete L. leaf extract was 13.2939%. The quality parameters of Crescentia cujete L. leaf extract included organoleptic tests such as thick extract, odor according to the plant of origin, brown color, water-soluble extract content of 11.54%, ethanol-soluble extract content of 12.49%, water content of 8.44%, and ash content of 4.12%. These results indicate that Crescentia cujete L. leaf extract meets the requirements according to the Indonesian Herbal Pharmacopoeia. The results of phytochemical screening of Crescentia cujete L. leaf extract indicate that Crescentia cujete L. leaf extract contains flavonoids, alkaloids, saponins, tannins, and steroids